Zinc ion sorption onto solution-precursor plasma-sprayed hydroxyapatite coatings via raman and X-ray photoelectron spectroscopies. Issue 6 (3rd July 2021) - Escobal, Mariel A.; Candidato, Rolando T.
Abstract: This paper reports the unusual ion sorption of zinc ions to the structure of solution-precursor plasma-sprayed hydroxyapatite coatings studied via X-ray photoelectron and Raman spectroscopy techniques. Raman peak deconvolution revealed no significant band shifting or peak broadening for 5 mol% and 10 mol% zinc-added hydroxyapatite coatings suggesting no distortion in the unit cell. The calculated bond length-wavenumber correlation also showed no significant changes in the bond length of the phosphate group after zinc addition. On the other hand, X-ray photoelectron spectroscopic analysis showed that a significant binding energy shift was observed for the calcium-oxygen and phosphorous-oxygen bonds when 10 mol% of zinc ion is added. It is likely that for low zinc concentration (5 mol%) in plasma-sprayed hydroxyapatite coating, zinc ions possibly inserted at the interstitial site of hydroxyapatite contrary to the presumed substitution at the calcium site. Such insertion did not disturb phosphate Raman signals and caused no shifting in the calcium-oxygen and phosphorous-oxygen Raman peaks. On the other hand, X-ray photoelectron spectroscopic analysis revealed a calcium deficient hydroxyapatite coating and significant peak shifting was observed when 10 mol% of zinc ion is added. The evolution of X-ray photoelectron spectroscopy peaks indicates that substitution of zinc ion in the calcium site is predominant for 10 mol% of zinc concentration. The substituted zinc ion forms a tetrahedral coordination with the phosphate group as revealed in X-ray photoelectron spectroscopic analysis.